Effects of Occupational Noise Exposure on Arterial Blood Pressure of Workers in Selected Industrial Places in Duhok City. - Yousif, Kamil M.; Mahdi, Berivan H. (Science Journal of University of Zakho, 2013)
Noise pollution is increasingly being recognized as a physical factor in the environment that is injurious to many aspects of health. Environmental noise induces alterations of various physiological responses in individuals exposed to it. The aim of the present study is to assess the effects of industrial noise on some aspects related to the cardiovascular system of workers exposed to industrial noise in the woodworking industry in Duhok city, Iraq. The sound levels of electrical saws can be as high as about 100 dB. The study group included 29 workers employed in the woodworking industry (Carpentry) exposed to industrial noise levels exceeding 95 dB. In order to observe the harmful effects of the noise caused by the Occupational Noise from the Carpentry machines, a questionnaire was made for all the workers (29 persons) included in this study. The results of this study showed significant changes in systolic blood pressure, diastolic blood pressure, mean arterial pressure, pulse pressure and pulse rate in the workers in the woodworking industry. Thus this study lead to conclude that industrial noise could be possible contributing factor in the development of arterial hypertension.